Tailoring the glassy mesophase range of thermotropic polyesters through copolymerization of 4, 4'-bibenzoate and kinked isomer. (1st February 2019) - Heifferon, Katherine V.; Mondschein, Ryan J.; Talley, Samantha J.; Moore, Robert B.; Turner, S. Richard; Long, Timothy E.
Abstract: The substitution of a linear biphenyl monomer with its meta isomer in liquid crystalline polyesters affords (co)polyesters with tunable liquid crystalline (LC) and thermomechanical properties. Melt transesterification afforded two (co)polyester series based on the semi-aromatic homopolymers poly(diethylene glycol 4, 4′ bibenzoate) and poly(butylene 4, 4′ bibenzoate) at high molecular weights. In each series, the linear dimethyl-4, 4′ bibenzoate (4, 4'BB) was systematically exchanged with its kinked isomer, dimethyl-3, 4′ bibenzoate (3, 4'BB). The incorporation of the meta isomer resulted in tunable crystalline and LC properties. Differential scanning calorimetry (DSC), wide angle X-ray scattering (WAXS), X-ray diffraction (XRD), and polarized optical microscopy (POM) elucidated that the kinked structure of 3, 4'BB disrupted crystallization at low incorporations, significantly lowering the melting transition temperature (>50 °C) in each series. The LC properties were less impacted due to the biphenyl structure resulting in LC glasses with wide mesogenic windows. Dynamic mechanical analysis (DMA) further demonstrated the tunable nature of the thermomechanical properties resulting from the (co)polymerization of these isomers. Graphical abstract: Highlights: Synthesized two liquid crystalline (co)polyesters utilizing isomeric comonomers. Liquid crystalline order and thermal properties investigated upon increased incorporation of kinked monomer. Liquid crystalline glass morphologies observed at high linear monomer compositions.